David Deutsch - works 1968-2017 - Ferguson, Bruce W. (Radius Books, 2018)
"This is the first retrospective on the paintings of New York-based artist David Deutsch (born 1943), spanning 50 years. Deutsch has used a variety of techniques--painting, sculpture, photography, drawing and mixed media--to create artwork that addresses complicated themes of the interior and exterior. From voyeuristic nighttime aerial photography to painterly abstracted landscapes, Deutsch wrestles with how we occupy our lives and the tension that exists as we navigate paths through time and memory. Most recently, Deutsch has focused primarily on painting large-scale monotypes, about which Roberta Smith of the New York Times notes, "Mr. Deutsch's paintings are grown-up, complex of space and surface, and rich in notions of human interaction or the lack thereof; voyeurism and solitude; and often an ambiguous ominousness." This extensive monograph provides a thorough look at a body of work that is at once innovative, familiar and provocative." -- Publisher's description
Includes bibliographical references
Keywords: Deutsch, David -- 1943-; Geschichte 1968-2017; Malerei; Deutsch, David / 1943 August 8- / Exhibitions; Painting, American / 20th century / Exhibitions; Painting, American / 21st century / Exhibitions; Photography / United States / 20th century / Exhibitions; Photography / United States / 21st century / Exhibitions; Bildband; Werkverzeichnis